Rotationally modulated variations and the mean longitudinal magnetic field of the Herbig Ae star HD 101412 - Hubrig, S. (2011)
Context. Despite the importance of magnetic fields to a full understanding of the properties of accreting Herbig Ae/Be stars, these fields have scarcely been studied until now over the rotation cycle. One reason for the paucity of these observations is the lack of knowledge of their rotation periods. The sharp-lined young Herbig Ae star HD 101412 with a strong surface magnetic field has become in the past few years one of the most well-studied targets among the Herbig Ae/Be stars. Aims. We present our multi-epoch polarimetric spectra of this star acquired with FORS 2 to search for a rotation period and constrain the geometry of the magnetic field. Methods. We measured longitudinal magnetic fields for 13 different epochs distributed over 62 days. These new measurements and our previous measurements of the magnetic field in this star were combined with available photometric observations to determine the rotation period. Results. We find the rotation period to be P = 42.076 ± 0.017 d. According to near-infrared imaging studies, the star is observed nearly edge-on. The star exhibits a single-wave variation in the longitudinal magnetic field during the stellar rotation cycle. These observations are usually considered as evidence of a dominant dipolar contribution to the magnetic field topology.